Interleukin 1‐alpha deficiency increases the expression of Follicle‐stimulating hormone receptors in granulosa cells. Issue 6 (17th April 2017) - Uri‐Belapolsky, Shiri; Miller, Irit; Shaish, Aviv; Levi, Mattan; Harats, Dror; Ninio‐Many, Lihi; Kamari, Yehuda; Shalgi, Ruth
Abstract : Follicle‐stimulating hormone receptor (FSHR) is a pivotal regulator of ovarian response to hormonal stimulation. Inflammatory conditions have been linked to lower FSHR expression in granulosa cells (GCs) as well as an attenuated response to hormonal stimulation. The current study aimed to reveal if deficiency and/or blockage of the pro‐inflammatory cytokine interleukin 1‐alpha (IL1A) increased Fshr expression in rodent GCs. We found elevated Fshr transcript abundance, as assessed by quantitative PCR, in primary GCs isolated from Il1a ‐knockout compared to wild‐type mice, and that the expression of FSHR is significantly higher in Il1a ‐knockout compared to wild‐type ovaries. Supplementing GC cultures with recombinant IL1A significantly lowered Fshr expression in these cells. In accordance with the Fshr expression pattern, proliferation of GCs was higher in follicles from Il1a ‐knockout mice compared to wild‐type mice, as indicated by the MKI67 immunohistochemical staining. Furthermore, treating wild‐type mice with anakinra, an IL1 receptor 1 antagonist, significantly increased the expression of Fshr in primary GCs from treated compared to control mice. These data highlight an important interdependency between the potent pro‐inflammatory cytokine IL1A and Fshr expression.